Variabel Aspek Kepuasan Berhuni Di Lingkungan Hunian Perkotaan, Kota Malang - Mustikawati, Triandriani; Ernawati, Jenny (RUAS (Review of Urbanism and Architectural Studies), 2014)
The satisfaction and perception on neighborhood is one of the most basic topic in Environmental Psychology. This research aims at exploring subjectif indicators of the urban neighborhood quality viewed through the perception of the residents on their neighborhood. The quality of the neighborhood is seen through 4 aspects: architecture and city planning, sosial relationship, public service and contextual aspect. 40 respondent were choosen from the newest telephone book by simple random sampling method. They respresent 5 districts in Malang city. The respondent were asked to answer the self-administered questioner that consist of semi-open questions about residential quality aspect, qualitatively. The method of analysis is descriptive statistic. The result showed 77 variables of residential satisfaction according to the residents perspective. These variables are divided into 4 aspects of the quality of neighborhood (architecture and city planning, sosial relationship, public service and contextual). It showed that beside physical aspects of environment, the residents also determine supportive non physical aspects as important aspects for their neighborhood.Keywords:residential satisfaction, urban neighborhood